Analisis Hukum Terhadap Tindak Pidana Pencemaran Nama Baik Dan Ujaran Kebencian Melalui Media Sosial - Ranti, Ranti Prasisca (Diktum: Jurnal Ilmu Hukum, 2021)
The Pelakor phenomenon which is now so viral in cyberspace. This research is related to Electronic Transaction Information which in Indonesia itself has many similar cases. The emotion felt by a legal wife towards Pelakor refers to expressions of hatred for the domestic problems she is experiencing, by expressing frustration on social media such as Facebook. This study seeks to answer questions regarding the factors that cause perpetrators to commit crimes and how judges consider the perpetrators of criminal acts of defamation and hate speech by the legal wife against PELAKOR through social media Facebook. The research method uses a normative and empirical juridical approach. The results of the study show that the cause of the perpetrators of committing criminal acts of crime. Individual psychological factors and public ignorance are the causes of hate speech crimes. The judge's consideration of the perpetrators of criminal acts of defamation and hate speech carried out by the legal wife against the perpetrator through social media Facebook, all elements were legally proven and convinced the reporting witness and expert witness to provide correct information and the defendant was proven to have fulfilled the elements or Article 45 paragraph ( 1) In conjunction with Article 27 paragraph (3) of the Law of the Republic of Indonesia Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.